In Vitro Lymphocyte Response to Purified Protein Derivative, BCG, and Mycobacterium leprae in a Population Not Exposed to Leprosy - Closs, Otto (1975)
Lymphocytes from 14 BCG-vaccinated donors, seven tuberculin positive and seven tuberculin negative by skin testing, were stimulated in vitro with four mycobacterial antigens, purified protein derivative (PPD), PPD/BCG, whole BCG bacilli, and whole Mycobacterium leprae and also with Candida antigen and phytohemagglutinin. The response was measured by incorporation of (3)H-labeled thymidine. The response to PPD, PPD/BCG, and BCG was found to correlate with the result of skin testing with turberculin. The turberculin-positive group also responded more strongly to M. leprae, whereas the two groups did not differ significantly in their response to Candida antigen or phytohemagglutinin. These findings indicate a certain degree of cross-reactivity between BCG and M. leprae. The use of the lymphocyte transformation test to measure antigenic cross-reactivity is discussed.